Amine Activation: N‐Arylamino Acid Amide Synthesis from Isothioureas and Amino Acids. Issue 14 (14th June 2017) - Zhu, Yan‐Ping; Mampuys, Pieter; Sergeyev, Sergey; Ballet, Steven; Maes, Bert U. W.
Abstract: N ‐arylamino acid amides have been synthesized via a novel method based on N ‐arylamine activation into isothioureas followed by reaction with amino acids under iron catalysis. The activated N ‐arylamines are easily prepared using a three‐component reaction with commercial reagents, tert ‐butylisocyanide and S ‐phenyl benzenethiosulfonate. The protocol shows a broad functional group compatibility, with respect to side chain functionality of the amino acid (e. g. aliphatic and aromatic OH, (hetero)aromatic NH, amide NH, thioether), and the chiral amino acids do not undergo epimerization. The mechanism of the new amide synthesis has been studied. Abstract :